THE EDUCATION IN ECONOMICS AT SHUMEN UNIVERSITY AT THE INTERSECTION BETWEEN EMPLOYERS AND STUDENTS: THE EDUCATION IN ECONOMICS AT SHUMEN UNIVERSITY AT THE INTERSECTION BETWEEN EMPLOYERS AND STUDENTS - Todorova, Korneliya (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The article is based on the idea that an improvement in the quality of education at Shumen University can be achieved only after surveying the opinions and evaluations of all concerned parties. The present study correlates the standpoints of students and employers regarding the quality of education within the Economics major at Shumen University. This way one of the main European principles for quality of education is observed - its self-evaluation.